A randomized controlled trial of web-based cognitive behavioral therapy for severely fatigued breast cancer survivors (CHANGE-study): study protocol. Issue 1 (December 2015) - Abrahams, H.; Gielissen, M.; Goedendorp, M.; Berends, T.; Peters, M.; Poort, H.; Verhagen, C.; Knoop, H.
Abstract Background About one third of breast cancer survivors suffer from persistent severe fatigue after completion of curative cancer treatment. Face-to-face cognitive behavioral therapy (F2F CBT), especially designed for fatigue in cancer survivors, was found effective in reducing fatigue. However, this intervention is intensive and treatment capacity is limited. To extend treatment options, a web-based version of CBT requiring less therapist time was developed. This intervention is aimed at changing fatigue-perpetuating cognitions and behaviors. The efficacy of web-based CBT will be examined in a multicenter randomized controlled trial. Methods In total, 132 severely fatigued breast cancer survivors will be recruited and randomized to either an intervention condition or care as usual (ratio 1:1). Participants will be assessed at baseline and 6 months thereafter. The intervention group will receive web-based CBT, consisting of three F2F sessions and maximally eight web-based modules over a period of 6 months. The care as usual group will be on a waiting list for regular F2F CBT. The total duration of the waiting list is 6 months. The primary outcome of the study is fatigue severity. Secondary outcomes are functional impairments, psychological distress and quality of life. Discussion If web-based CBT is effective, it will provide an additional treatment option for fatigue in breast cancer survivors. Web-based CBT is expected to be less time-consuming for therapists than regular F2F CBT, which would result in an increased treatment capacity. Moreover, the intervention would become more easily accessible for a larger number of patients, and patients can save travel time and costs. Trial registration Dutch Trial Registry -NTR4309